Beauty queens [compact disc, uanbridged] - Bray, Libba (Scholastic Audiobooks, 2011)
When a plane crash strands thirteen teen beauty contestants on a mysterious island, they struggle to survive, to get along with one another, to combat the island's other diabolical occupants, and to learn their dance numbers in case they are rescued in time for the competition.